Studi Deskriptif Representasi Matematis Mahasiswa pada Materi Luas Daerah dengan Pendekatan Integral - Sumargiyani (Efektor, 2025)
This study aims to describe the mathematical representation ability of Mathematics Education students at Universitas Ahmad Dahlan in solving problems related to the area of plane regions using an integral approach. This research employs a descriptive quantitative method with 23 students as subjects. The data were collected from the documentation of the Final Semester Examination (UAS) in the Integral Calculus course, which included questions on the area of plane regions. Data analysis was conducted using a mathematical representation scoring rubric. The results showed that the students’ mathematical representation abilities varied, with 39.13% categorized as high, 26.09% as medium, and 34.78% as low. The average score was 59.78, with a standard deviation of 37.73, a maximum score of 100, and a minimum score of 10. These findings indicate that the students’ mathematical representation ability is still relatively low and uneven across the three aspects of representation. The most common errors included visual errors in drawing area graphs, verbal errors in explaining mathematical procedures, and symbolic errors in algebraic manipulation and the use of mathematical symbols.